Attitudes of teenagers towards sexuality - Anes, Eugénia (2016)
The area of sexuality is seen as very relevant at any stage of life, but with speciic characteristics in adolescence. Attitudes, behaviors, beliefs and values related to sexuality in the life cycle stage, are factors that can inluence the health of adolescents, affecting the integrity of the various levels of functionality. To know the attitudes of teenagers towards sexuality and analyze its relationship with gender and religion. It is a study of quantitative approach, observational, descriptive and analytical. A questionnaire was applied on a sample of 432 adolescents aged between 14 and 18 years. The results show that most young people presents more liberal positions and less conservative towards sexuality positions. The girls expressed more liberal attitudes compared to boys. The girls value more affective dimension. With regard to religion, the attitudes of teenagers towards sexuality Catholics no are different from non-Catholic teens. Although in recent years there had been changes in cultural patterns, which are relected in a relative change of mentalities, we found that sexuality in general still remains associated with myths and taboos. Teens revealed liberal attitudes about sexuality in general, but also show fear, shame and embarrassment regarding their sexuality and embarrassment in communicating about it.